1990
DOI: 10.1093/jmedent/27.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Comparison of the Leishmania Vectors Phlebotomus papatasi and P. langeroni (Diptera: Psychodidae)

Abstract: Cellulose acetate electrophoresis was employed to detect 22 different enzyme systems in laboratory-reared populations of the sympatric Leishmania vectors, Phlebotomus papatasi (Scopoli) and P. langeroni Nitzulescu. Electrophoretic conditions sensitive enough to permit as many as eight separate enzyme assays to be performed on individual specimens were developed. Under these conditions, 18 enzymes were detected with high resolution and regularity. Evidence was obtained which suggested that a number of enzymes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…1). Some populations, like those from Palestine, Israel and Egypt, were selected based on previous isoenzyme studies (Kassem et al , 1990) that suggested the presence of genetic polymorphism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Some populations, like those from Palestine, Israel and Egypt, were selected based on previous isoenzyme studies (Kassem et al , 1990) that suggested the presence of genetic polymorphism.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of methods have been employed in the past to evaluate spatial components of genetic diversity among P. papatasi populations. Genomic allele frequency estimates have been used to calculate genetic diversity using allozyme (Kassem et al , 1990, 1993), mtDNA (Parvizi et al , 2003) and microsatellite loci (Hamarsheh et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The latter authors have demonstrated that the electrophoretic mobility of carboxylesterases associated with organophosphate-resistance in Culex pipiens mosquitoes can be affected by proteolytic degradation during the preparation of homogenates (Callaghan et al 1994). This phenomenon has not been described for phlebotomine sand ßies despite the use of EST patterns in many taxonomical and genetic surveys: in the Old World Phlebotomus genus, EST isozymes have been shown to distinguish sympatric and related species of Larroussius and Phlebotomus subgenera (Kassem et al 1990, Madulo-Leblond et al 1991, Benabdennbi Cherkaoui 1998, Ghosh et al 1999.…”
mentioning
confidence: 99%
“…reported the presence of polymorphisms at many isoenzyme loci among populations of P . papatasi from Egypt but no significant genetic differentiation could be detected [17,18]. It must be stressed that the possibility of genetic differentiation in P .…”
Section: Introductionmentioning
confidence: 99%